Determination of Trace Cadmium in Food Samples by Electrothermal Atomic Absorption Spectrometry After Cloud Point Extraction - Xiang, G.Q.; Wen, S.P.; Wu, X.Y.; Liu, Y.L.; Jiang, X.M.; He, L.J. (Asian Journal of Chemistry, 2010)
A new method for the determination of trace cadmium in food samples by cloud point extraction combined with electrothermal atomic absorption spectrometry is presented and evaluated. The method based on the fact that formation of a hydrophobic complex of cadmium(II) with ammonium pyrrolidine dithiocarbamate at pH 4.0 and subsequently enter surfactant-rich phase. Cadmium(II) in surfactant-rich phase was determined by electrothermal atomic absorption spectrometry after dilution by 0.2 mL nitric acid in methanol (0.1 mol L-1). The main factors affecting the cloud point extraction, such as pH, concentration of ammonium pyrrolidine dithiocarbamate and Triton X-114, equilibrium temperature and incubation time, sample volume were investigated in detail. Under the optimum conditions, the limit of detection of this method was 0.004 ng mL-1 for cadmium and the relative standard deviation was 4.3 % (c = 0.5 ng mL-1, n = 7). The analytical results for the certified reference rice sample (GBW08510) were in a good agreement with the certified value. The proposed method was successfully applied to determination of trace cadmium in the liquor, rice and drinking water with satisfactory results.